(untitled) (International Conference on Education, Psychology and Humanities, 2026)
Portrait is the verbal depiction of a character’s external appearance.1 When a writer creates a literary work, they introduce a variety of characters, or through them, reflect on the environment, life, and attitudes surrounding these figures. In the theory of literary translation, adequately recreating character portraits is considered one of the most challenging tasks. This is because portraying a character’s portrait involves not only describing their physical appearance but also encapsulating their inner world, psychological state, social status, and the author’s attitude toward them. When depicting a character in a work, the author introduces the reader to the character’s portrait and inner experiences. Johann Wolfgang von Goethe’s “Die Wahlverwandtschaften” is particularly significant in this regard, as its portrait descriptions are distinguished by psychological depth and symbolism. In the second section of this chapter, the main translation methods used in rendering the portraits of characters in the work are analyzed, including lexical-semantic transformations, stylistic adaptation, emotional-expressive equivalence, and compensation techniques. It is essential that a translator, when undertaking the translation of a literary work from one language into another, aims to fully convey the idea and content of the work to the reader. That is, the translator must reflect in detail all the images, character portraits, personality traits, complexities, speech, and events associated with the characters in the translation.